They found a cave - Chauncy, Nan, 1900-1970.; Horder, Margaret (London : Oxford University Press, 1949)
Some adventurous children run away from unpopular guardians to live in a cave in the Tasmanian bush, where they meet a bushman they nick-name "Mad Dad" and discover an unusual treasure.
For children.
Keywords: Children -- Tasmania -- Conduct of life -- Juvenile fiction; Country life -- Tasmania -- Juvenile fiction; Caves -- Tasmania -- Juvenile fiction; Children's stories, Australian; Adventure stories